Evaluation of the Quantitative and Qualitative Alterations in the Fatty Acid Contents of the Sebum of Patients with Inflammatory Acne during Treatment with Systemic Lymecycline and/or Oral Fatty Acid Supplementation - Adilson Costa; Aline Siqueira Talarico; Carla de Oliveira Parra Duarte; Caroline Silva Pereira; Ellem Tatiani de Souza Weimann; Lissa Sabino de Matos; Livia Carolina Della Coletta; Maria Carolina Fidelis; Thaísa Saddi Tannous; Cidia Vasconcellos (Hindawi Limited, 2013)
Background. Acne is a dermatosis that involves an altered sebum pattern. Objectives. (1) To evaluate if a treatment based on antibiotics (lymecycline) can alter fatty acids contents of the sebum of patients with acne; (2) to evaluate if oral supplementation of fatty acids can interfere with fatty acids contents of the sebum of patients with acne; (3) to evaluate if there is any interaction in fatty acids contents of the sebum of patients with acne when they use both antibiotics and oral supplementation of fatty acids. Methods. Forty-five male volunteers with inflammatory acne vulgaris were treated with 300 mg of lymecycline per day, with 540 mg of γ-linolenic acid, 1,200 mg of linoleic acid, and 510 mg of oleic acid per day, or with both regimens for 90 days. Every 30 days, a sample of sebum from the forehead was collected for fatty acids' chromatographic analysis. Results. Twelve fatty acids studied exhibited some kind of pattern changes during the study: C12:0, C14:0, C15:0, C16:1, C18:0, C18:1n9c+C18:1n9t, C18:2n6t, C18:3n6, C18:3n3, C20:1, C22:0, and C24:0. Conclusions. The daily administration of lymecycline and/or specific fatty acids may slightly influence some fatty acids levels present in the sebum of patients with inflammatory acne vulgaris.